Simultaneous Quantification of 17 Cannabinoids in Cannabis Inflorescence by Liquid Chromatography-Mass Spectrometry - Amitha K. Hewavitharana; Francine Gloerfelt-Tarp; Matthew Nolan; Bronwyn J. Barkla; Sarah Purdy; Tobias Kretzschmar (Separations, 2022)
With an increasing appreciation for the unique pharmacological properties associated with distinct, individual cannabinoids of Cannabis sativa, there is demand for accurate and reliable quantification for a growing number of them. Although recent methods are based on highly selective chromatography-mass spectrometry technology, most are limited to a few cannabinoids, while relying on unnecessarily sophisticated and expensive ultra-high performance liquid chromatography and tandem mass spectrometry. Here we report an optimised, simple extraction method followed by a reliable and simple high performance liquid chromatography method for separation. The detection is performed using a time-of-flight mass spectrometer that is available in most natural products research laboratories. Due to the simplicity of instrumentation, and the robustness resulting from a high resolution in the chromatography of isobaric cannabinoids, the method is well suited for routine phytocannabinoid analysis for a range of applications. The method was validated in terms of detection and quantification limits, repeatability, and recoveries for a total of 17 cannabinoids: detection limits were in the range 11–520 pg when using a 1 µL sample injection volume, and the recovery percentages ranged from 85% to 108%. The validated method was subsequently applied to determine cannabinoid composition in the inflorescences of several medicinal Cannabis sativa varieties.